A profile of disciplinary history: Academic career and male power in the personal archive of historian Adeline Daumard - Machado, Daiane [UNESP] (Sociedade Brasileria de Teoria e Historia de Historiografia, 2021)
This paper examines how the personal archive of the French historian Adeline Daumard shapes a profile of the discipline of History. When approaching some elements of Daumard’s daily work as a historian in relation to the sexual tensions constituting the disciplinary field, her experiences highlight the complexity of being a woman in the French academic environment. In profiling and grouping personal archival cultures, we also verified an evident intimacy between Daumard and Brazil, where the author is welcomed by a female intellectual network that dialogues with her way of making history and boosts her career. Mobilizing gender as a lens of perception, we walk through Fonds Daumard, deposited in the French Archives Nationales, sexualizing its corpus to observe how social roles are displayed in this space and signify power relations that delegitimize female academic careers.
Um perfil da história disciplinar: Carreira acadêmica e poder masculino no arquivo pessoal da historiadora Adeline Daumard
Keywords: Brazilian historiography; French historiography; Gender